Skin rashes and stomatitis due to parenteral treatment of rheumatoid arthritis with sodium aurothiomalate. Issue 3 (March 1992) - Svensson, A; Theander, J
Abstract : In a prospective study of 45 patients with rheumatoid arthritis mucocutaneous symptoms and signs were evaluated before and during treatment with intramuscular sodium aurothiomalate (Myocrisin). The work, performed in close collaboration between dermatology and rheumatology departments, showed that there was no significant increase in mucocutaneous side effects in patients with pre-existing mucocutaneous disease. It is concluded that pre-existing dermatitis is not a contraindication for treatment with gold salts and that a previous mucocutaneous reaction to gold salts is not an absolute contraindication for a new trial of chrysotherapy.